Modification of Ti/TiO2NT with ZrO2 nanoparticles to enhance photoelectrocatalytic performance in removal of dibutyl phthalate - Hyppólito, Marina Paz [UNESP]; Perini, João Angelo Lima [UNESP]; da Silva, Bianca Ferreira [UNESP]; Jorge, Sônia Maria Alves [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Springer Nature, 2022)
This work shows that ZrO2, used as a modifier of TiO2, can be highly effective as a co-catalyst in the photoelectrocatalytic degradation of dibutyl phthalate (DBP). The monoclinic phase of ZrO2 was easily obtained by chemical deposition on TiO2 nanotubes (Ebg ~3.06 eV), increasing the occurrence of hydroxyl groups and acidity on the surface of the material, as observed by electrophoretic mobility measurements. The optimized photoelectrocatalysis conditions were bias potential of 1.5 V, 0.1 M Na2SO4 (initial pH 6) supporting electrolyte, 6 ppm of DBP, and UV/Vis irradiation. These conditions resulted in complete removal of DBP, down to the limit of detection of the chromatographic method used, with up to complete TOC removal after 60 min of treatment. The effects of pH, bias potential, DBP concentration, and applied potential were investigated. The method was compared with photocatalysis and photolysis. An oxidation mechanism is proposed, based on intermediates detected by LC-MS/MS during 10 min of photoelectrocatalysis.
Keywords: Degradation; Dibutyl phthalate; Endocrine disruptors; Photoelectrocatalysis; Photoelectrodes; TiO2 nanotubes